The Structural Violence of Imperial Trusteeship in Postcolonial Governmentality - Allsobrook, Christopher (African studies (Johannesburg), 2025)
The article considers how structural violence in African polities has displaced sovereign agency and responsibility for its harmful effects by extending imperial practices of trusteeship in postcolonial governmentality. It explains how, with liberation, decolonisation and political independence, imperial practices of indirect rule and informal empire - legitimised with reference to trusteeship - have resulted in practices of domination, which are instantiated in structural violence. Trusteeship formally displaces the direct agency of coercive imperial colonisation, first, by disguising it as protection and development assistance, and second, by setting up proxy domestic political agents to stand in for absent imperial sovereignty. I analyse these dynamics with reference to Foucault's account of governmentality and his theories of power to explain African complicity with empire. I then review and critique Mbembe's analysis of necropolitics in the postcolony to explain a weakness in his account, which leads him to misconstrue these conflicts in terms of sovereign power, thereby misrepresenting the agency of the consequent African victims of postcolonial structural violence, without pointing to any way out. To correct this misunderstanding, and to identify a basis for emancipatory agency in Africa, I turn to Biko's critical analysis of Black governmentality under apartheid, which points forward to postcolonial empowerment.